(untitled) (Asean Journal of Engineering Education, 2025)
This paper explores the integration of the Book-End Division Approach with ClassPoint within the Technology-Enhanced Learning (TEL) framework to enhance student engagement in Digital Electronics courses at the Faculty of Electrical and Electronics Engineering Technology (FTKEE), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA). Conventional teaching methods frequently face challenges to engage students, particularly in technical disciplines like electrical and electronic engineering. The study leverages a student engagement framework to foster an interactive learning environment, utilizing ClassPoint’s interactive features to promote active participation, and collaboration among students. The Book-End Division Approach divides class sessions into advanced organizing, intermittent discussions, and closure. Results indicate significant impacts in student participation and motivation, with over than 90% of the students agree ClassPoint TEL made the classroom environment more motivating.